THE IMPLEMENTATION OF TEACHING READING BY USING STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) TECHNIQUE AT MTsN MOJOROTO KOTA KEDIRI - Mashadi, Ali (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 6 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This research is aimed to know from the result of implementation STAD technique in teaching reading at MTsN Mojoroto Kediri. Descriptive qualitative approach is used to do this research. The instrument used in this research is interview, observation of teaching learning process and documentation. Interview is done to get data about the process of implementation in teaching. Observation is done to know the steps of teaching learning. The result shows that (1) STAD can be implemented to teach reading in MTsN Mojoroto Kediri. (a) Teaching reading using STAD technique can improve students’ participation and competence in reading comprehension. (b) The teacher always prepares the scenario of teaching learning activity into lesson plan. (c) Step of teaching using STAD technique is similar as the theory and it has been written in lesson plan. (2) The reason of implementing STAD in teaching reading is to prove whether STAD technique can increase at comprehension and ability students in reading.(3) There are some problems faced by the teacher when implementing STAD in the class. Especially comes from the teacher and student such as to make a group according to ability every student. (4) The students’ reading comprehension before being taught by using STAD technique is under the criteria of success. The average score before being taught by using STAD is 74.53 and it increases become 84.06 in the score after being taught by using STAD method. It means that STAD is effective to be used in teaching reading. But, after being taught by using STAD technique, the achievement grows higher and can reach the criteria of success that is 75.00. Therefore, this is one of techniques suggested for the teacher to make it simple in teaching reading.(4) STAD technique proven to increase ability and comprehension at the students. It result significantly supports teaching reading in the class.